Insight into the evolutionary history of freshwater sponges: A new genus and new species of Spongillida (Porifera: Demospongiae) from Upper Cretaceous (Maastrichtian) Deccan intertrappean lacustrine deposits of the Malwa Group, Central India. (October 2021) - Samant, Bandana; Pronzato, Roberto; Mohabey, Dhananjay Mahendrakumar; Kumar, Deepesh; Dhobale, Anup; Pizal, Priya; Manconi, Renata
Abstract: New fossil freshwater sponges are recorded from the Upper Cretaceous (Maastrichtian) intertrappean lacustrine sediments of Malwa Group associated with Deccan volcanic province in Central India. The micro-palaeontological analysis of diagnostic spicular morphotraits supports the ascription of these fossils to the order Spongillida. The description of new genus Palaeocorvospongilla (family Palaeospongillidae) is based on the entire spicular complement of Palaeocorvospongilla cretacea gen. et sp. nov. It is distinguished from other extant and fossil Spongillida by pseudobirotules and oxeas with morphometries, indicating a very large size of skeletal microscleres from Deccan intertrappean fossils. From an evolutionary point of view, data on Indian fossils indicate a clear trend of long term conservative morphology in the evolutionary history of this genus since the Upper Cretaceous. Fossil data also indicate an early splitting (Mesozoic) and spreading of freshwater sponges Spongillida taxa in the Asian continent.